Synergistic Interactions Between Direct and Indirect Bypasses in Combined Procedures: The Significance of Indirect Bypasses in Moyamoya Disease. Issue 2 (19th January 2017) - Uchino, Haruto; Kim, Jae-Hoon; Fujima, Noriyuki; Kazumata, Ken; Ito, Masaki; Nakayama, Naoki; Kuroda, Satoshi; Houkin, Kiyohiro
Abstract: BACKGROUND: Whether additional indirect bypasses effectively contribute to revascularization in combined procedures remains unclear in patients with moyamoya disease. OBJECTIVE: To evaluate the longitudinal changes associated with combined procedures while following up pediatric and adult patients long term and to assess whether any other clinical factors or hemodynamic parameters affected these changes to determine an optimal surgical strategy. METHODS: We studied 58 hemispheres in 43 adults and 39 hemispheres in 26 children who underwent combined revascularization for moyamoya disease. To evaluate bypass development, we assessed the sizes of the superficial temporal artery and middle meningeal artery using magnetic resonance angiography. Multivariate analysis determined the effects of multiple variables on bypass development. RESULTS: Indirect bypass (middle meningeal artery) development occurred in 95% and 78% of the pediatric and adult hemispheres, respectively. Of these, dual development of direct and indirect bypasses occurred in 54% of the pediatric hemispheres and in 47% of the adult hemispheres. Reciprocal superficial temporal artery regression occurred in 28% of the hemispheres during the transition from the postoperative acute phase to the chronic phase during indirect bypass development. Good indirect bypass development was associated with adult hemispheres at Suzuki stage 4 or greater (odds ratio, 7.4; 95% confidence interval, 1.4-39.4; P = .02). Disease onset type and preoperative hemodynamic parameters were not considered predictors for the development of surgical revascularization. CONCLUSION: Simultaneous direct and indirect bypass development was most frequently observed, regardless of patient age and hemodynamic status. Applying indirect bypass as an adjunct to direct bypass could maximize revascularization in adults and children.